8. OPERATIONS RESEARCH MODEL IN CONVENTIONAL MILITARY DECISION-MAKING - Farrid Hidayat; Suroso; Farrith; Dikatama Tsania; Muchammad Furqon; Sudhibiyo; Ditasania (Staf Komunikasi dan Elektronika, TNI Angkatan Udara, 2026)
This study aims to analyze the robustness and risk of military decisions through theapplication of an operations research model based on sensitivity analysis. Conventional militarydecision-making has historically relied on doctrine, experience, and the intuition of commanders.This approach is adaptive, but has limitations in testing the resilience of military decisions tochanges in strategic and operational parameters. The research methodology uses a quantitativeapproach with operations research modeling and sensitivity testing for key parameters such astime, cost, and risk. The main results indicate that military decisions based on operationsresearch models have a more consistent level of robustness than conventional approaches. Thestudy's conclusions confirm that operations research models play an effective role as objectiveand measurable military decision-support systems. This research contributes to strengtheningthe systems and decision science approaches in the study of conventional military decisionmaking.